Social Aspects of Establishing Energy Cooperatives - Justyna Orłowska; Małgorzata Suchacka; Łukasz Trembaczowski; Robert Ulewicz (Energies)
The aim of this research was to investigate the social conditions of the implementation of energy cooperatives in Poland as a demand-side policy tool to reduce carbon emissions. Qualitative empirical research was conducted, including interviews with members and leaders of energy cooperatives as well as experts, to assess the effectiveness of new legal regulations concerning energy cooperatives. This study shows that the negative historic connotations with cooperatives do not impede the readiness of Poles to create energy cooperatives. They are open to innovation and are willing to cooperate for energy stability, which seems to be the most important factor determining involvement in energy cooperatives. The results also highlight significant barriers for the development of energy cooperatives, such as regulatory constraints and a lack of true incentives. Energy cooperatives have the potential to popularize renewable energy sources in Poland, but their growth requires better adaptation of legal regulations and greater political support.